Evaluation of the antiseptic effect of nanoemulsion with cinnamon essential oil on Streptococcus mutans (Research, Society and Development, 2022)
The objective of this work was to verify the antibacterial activity of nanoemulsion with essential oil (EO) of cinnamon (Cinamomum cassia), as a mouthwash. Two formulations of mouthwash containing cinnamon EO were developed for the preparation of nanoemulsions with two types of surfactants, Tween 80 and soy lecithin. Treatments were compared with chlorhexidine (control) for Minimum Inhibitory and Bactericidal Concentrations (MIC and MBC, respectively), synergism between treatments and kinetics of antimicrobial activity against Streptococcus mutans, in addition to quantifying the substantivity of the treatments. Together, the chemical characterization of cinnamon EO and the characterization of the nanoemulsions were carried out. The nanoemulsions showed antimicrobial activity in the MIC and CBM of 0.625 mg mL-1 against Streptococcus mutans and 0.01 mg mL-1 of chlorhexidine and no synergism was detected between each cinnamon EO nanoemulsion and chlorhexidine. Comparing the efficiency of nanoemulsions with 0.12% chlorhexidine in quantifying substantivity, there was no significant difference between treatments.